DECENT CONDITIONS AND PAYMENT OF THE COUNTRY'S INTELLECTUAL POTENTIAL IS THE KEY TO THE DEVELOPMENT OF EDUCATION AND SCIENCE - N. M., Vapnyarchuk (Київський національний університет імені Тараса Шевченка, 2022)
The article examines the current issues of the development of national education and science, since the problem of the quality of education and science in Ukraine has never had such an important social, economic and technical significance as at present, especially the issue of decent conditions and remuneration of the intellectual potential of the country as a factor of development education and science. It is noted that the state of affairs in the field of domestic education and science, the pace and depth of transformations do not fully satisfy the needs of the individual, society and the state, this is especially noticeable today, when the war that the Russian Federation has unleashed against Ukraine continues. Attention is drawn to the fact that in the conditions of the formation and development of a market economy in Ukraine, the need for highly qualified personnel and their professionalization is becoming increasingly acute. After all, the results of the activity of any sphere depend on the level of training of its employees, which means – on the state of the educational sphere, on its readiness to meet the needs of the real economy, society as a whole and each individual, in particular. It was concluded that the priority directions of educational and scientific policy should be the development, adoption and implementation of decisions aimed at preserving and developing the personnel potential of education and science, ensuring its vital activity, establishing order and procedures that determine the most effective use of human resources. The goal of modernization of education and science in Ukraine should be the creation of such a model of the educational and scientific process in which the best domestic and foreign traditions would be optimally combined. The creation of decent working conditions, decent pay, proper, safe and healthy working conditions is of great importance in this process, as this is a tangible step towards overcoming economic and social difficulties. Since the policy of low wages in the educational and scientific spheres leads to workers looking for work in other types of economic activity with a higher level of wages and migration abroad.

У статті досліджено актуальні питання розвитку вітчизняної освіти і науки, оскільки ніколи ще проблема якості освіти і науки в Україні не мала такого важливого соціального, економічного і технічного значення, як у теперішній час, особливо питання гідних умов та оплати праці інтелектуального потенціалу країни як фактору розвитку освіти і науки. Зазначено, що стан справ у галузі вітчизняної освіти і науки, темпи та глибина перетворень не повною мірою задовольняють потреби особистості, суспільства і держави, особливо це відчутно сьогодні, коли триває війна, яку російська федерація розв’язала проти України. Звернено увагу, що в умовах становлення та розвитку в Україні ринкової економіки все гострішою постає потреба у висококваліфікованих кадрах, у їх професіоналізації. Адже результати діяльності будь-якої сфери залежать від рівня підготовки її працівників, а це значить – від стану освітньої сфери, від її готовності задовольняти потреби реальної економіки, суспільства в цілому і кожної особистості, зокрема. Зроблено висновок, що пріоритетними напрями освітньої та наукової політики повинно бути вироблення, прийняття та реалізація рішень, спрямованих на збереження і розвиток кадрового потенціалу освіти і науки, забезпечення його життєдіяльності, встановлення порядку і процедур, що визначають найбільш ефективне використання людських ресурсів. Метою модернізації освіти і науки в Україні повинно стати створення такої моделі освітнього і наукового процесу, в якій би оптимально поєдналися кращі вітчизняні й зарубіжні традиції. Важливого значення у цьому процесі набуває створення гідних умов праці, гідної оплати праці, належних, безпечних і здорових умов праці, так як це відчутний крок до подолання економічних і соціальних труднощів. Оскільки політика низької заробітної плати в освітній і науковій сфері веде до пошуку працівниками роботи в інших видах економічної діяльності з вищим рівнем оплати праці та міграції за кордон.
ГІДНІ УМОВИ ТА ОПЛАТА ПРАЦІ ІНТЕЛЕКТУАЛЬНОГО ПОТЕНЦІАЛУ КРАЇНИ – ЗАПОРУКА РОЗВИТКУ ОСВІТИ І НАУКИ
Keywords: sphere of education; scientific sphere; constitutional regulation; social rights; intellectual potential; state; relations in the sphere of education and science; decent wages; human capital; innovations.; сфера освіти; наукова сфера; конституційне регулювання; соціальні права; інтелектуальний потенціал; держава; відносини в сфері освіти і науки; гідна оплата праці; людський капітал; інновації.